Ethnobotanical study in the underexplored species of Genus Litsea (Lauraceae) in Northern Thailand - NATCHA CHAISOUNG; PRATEEP PANYADEE; CHUNLIN LONG; CHATCHAI NGERNSAENGSARUAY; TANAWAT CHAOWASKU; ANGKHANA INTA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Chaisoung N, Panyadee P, Long C, Ngernsaengsaruay C, Chaowasku T, Inta A. 2023. Ethnobotanical study in the underexplored species of Genus Litsea (Lauraceae) in Northern Thailand. Biodiversitas 24: 3977-4000. Ethnobotanical studies offer valuable insights into medicinal plant use, but accuracy is limited by the difficulty in identifying similar species during field surveys. This study aims to investigate the Genus Litsea Lam. (Lauraceae) plants in Thailand, specifically focusing on underexplored species with ethnobotanical value for future utilization. The present research aims to comprehensively analyze the ethnobotanical data by comparing the results from previous ethnobotanical documents with those obtained from our field surveys. From a comprehensive review of ethnobotanical documents published from 1996-2022, the study discovered seven species of Litsea report to be used in Thailand. In addition, a subsequent field survey from November 2019 to December 2021 revealed that 13 species were used, with 11 of these used for medicinal purposes. The study identified seven additional species not previously documented for their medicinal uses. Among these species, Litsea mollis Hemsl., Litsea glutinosa (Lour.) C.B.Rob. and Litsea martabanica (Kurz) Hook.fil. have the highest use values and hold potential for future development, particularly L. mollis and L. martabanica. We also found that Litsea species were primarily used for treating digestive disorders. This study highlighted the importance of considering taxonomic complexities and conducting field surveys to assess plant uses accurately and can serve as a foundation for future research on these species, including their chemical analysis, biological activities, and pharmacological properties.